UK wildlife recorders cautiously welcome range‐shifting species but incline against intervention to promote or control their establishment - James Cranston; Sarah L. Crowley; Regan Early (People and Nature, 2022)
Abstract The global redistribution of species due to climate change and other anthropogenic causes is driving novel human–wildlife interactions with complex consequences. On the one hand, range‐shifting species could disrupt recipient ecosystems. On the other hand, these species may be contracting in their historic range, contributing to loss of biodiversity there. Given that arriving range‐shifting species could also perhaps have positive effects on recipient ecosystems, there is [in principle] a net benefit equation to be calculated. Thus, public opinion on these species may be divided and they may present a unique challenge to wildlife management. We surveyed the opinion of wildlife recorders about the establishment and management of eight birds and eight insects whose ranges have recently shifted into the United Kingdom. We asked whether respondents' attitudes were explained by the species' or respondents' characteristics, and whether or not climate change was emphasised as a cause of range‐shift. We also conducted qualitative analysis of the recorders' text responses to contextualise these results. Attitudes to range‐shifting species were mostly positive but were more ambivalent for less familiar taxa and for insects compared with birds. Respondents were strongly opposed to eradicating or controlling new range‐shifters, and to management aimed to increase their numbers. Whether climate change was presented as the cause of range‐shifts did not affect attitudes, likely because respondents assumed climate change was the driver regardless. These findings suggest that it will be difficult to generate support for active management to support or hinder species' redistribution, particularly for invertebrate or overlooked species among wildlife recorders. However, the positive attitudes suggest that on the whole range‐shifting species are viewed sympathetically. Engaging with wildlife recorders may represent an opportunity to garner support for conservation actions which will benefit both currently native and arriving species, such as improvements to habitat quality and connectivity. Read the free Plain Language Summary for this article on the Journal blog.